2006
DOI: 10.1002/bit.20928
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected improvement in stability and utility of cytochrome c by solution in biocompatible ionic liquids

Abstract: Proteins generally are only stable in vitro for short periods of time. This results in challenges during isolation and purification of recombinant proteins and reduces the shelf life of protein-based pharmaceuticals. Here we show that certain novel, biocompatible ionic liquids provide a stabilizing solvent for proteins, for example, cytochrome c, such that structure and activity are maintained even after 6 months of storage at room temperature. Normally, this protein would be rendered inactive after only 1 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
169
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(184 citation statements)
references
References 27 publications
9
169
0
4
Order By: Relevance
“…[19][20][21][22] In addition, they act as solvents or catalysts for various organic reactions. 23,24 Similarly, RTILs with the hydroxyl groups have CO2 absorption, [25][26][27][28][29] and cellulose/protein dissolution abilities.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] In addition, they act as solvents or catalysts for various organic reactions. 23,24 Similarly, RTILs with the hydroxyl groups have CO2 absorption, [25][26][27][28][29] and cellulose/protein dissolution abilities.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, room-temperature molten salts, usually referred to as "ionic liquids" (ILs), have become of interest as co-solvents for water, [1] in biphasic systems, [1] and as neat solvents. [1,2] ILs comprise organic cations, such as alkyl-substituted imidazolium, pyrrolidinium, and tetraalkylammonium ions, combined with a variety of anions defined later in this paper. For the major families of cations and anions see a review by Forsyth et al [3] In view of the growing importance of ILs, it is desirable to systematize the ion effects on enzyme properties such as stability, activity, and enantioselectivity.…”
mentioning
confidence: 99%
“…8 For example, extended stability of cytochrome C was observed in hydrated choline dihydrogen phosphate (HyCDHP). 14 Several other studies have reported similar beneficial effects for mushroom tyrosinase, 15 ribonuclease A, 16 interleukin-2 17 and even DNA in hydrated choline ILs. 18 Moreover, ILs based on the choline cation are now commonly used in many applications for which biocompatibility is an essential requirement, i.e.…”
Section: Introductionmentioning
confidence: 75%